MEANINGFUL LEARNING OF BIOMECHANICAL CONCEPTS: AN EXPERIENCE WITH PHYSICAL EDUCATION TEACHERS IN CONTINUING EDUCATION - Rachel Belmont; Duane Knudson; Paula Hentschel Lobo da Costa; Evelyse dos Santos Lemos (Journal of Physical Education)
ABSTRACT Biomechanical knowledge is essential for professional practice of physical education teachers, but it is still little applied by them. This study examined the effectiveness of a continuing education program based on meaningful learning theory to improve understanding of biomechanical principles and their application by physical education teachers. A pedagogical intervention study was developed using a mixed methods approach. Statistical analysis was performed to compare pretest and post-test scores, and content analysis to categorize the teachers' evaluation of classes. The program created significant increases in mastery of biomechanical concepts in teachers studied who had strong perceptions of the course, peer interaction, and application to professional practice. Difficulties perceived were related to lack of time to study and prior biomechanical knowledge.